(untitled) (Research, Society and Development, 2019)
The objective of this research was to identify the students’ perception of the Agricultural Technical Course, of the Federal Institute of Education, Science and Technology of Mato Grosso, Campus Campo Novo do Parecis (IFMT), on the transfer of technology from minimum processing of food to small farmer. As methodological procedures, we used: interview with structured script; technical visit to a small rural property, and intervention through theoretical lecture on Minimally Processed Foods (MPF) and Technology Transfer (TT). The present study stimulated students to develop a critical sense through contact with the small rural producer, whom they considered important for their professional formation. The methodology used (theoretical class on AMP and TT, as well as the Technical Visit to a small rural producer) contributed with the teaching of 90.48% of the students sampled. The students’ conceptions, through their reports, refer to the advantages of the MPF for the consumer, regarding practicality, being able to be related to the theoretical lecture given by the researcher.